Social Support Positively Correlated with Dietary Adherence among Patients with Hypertension in Primary Health Center - Hanifah Hanifah; Karina Megasari Winahyu; Muhammad Imam Muttaqin (Faletehan Health Journal, 2021)
Dietary adherence is one of the requirements in chronic disease management, which the success of hypertension management may correlate with the social support perceived by the patients. The study aimed to identify the relationship between social support and dietary adherence among patients with hypertension in Primary Health Centre, Tangerang. The study was a descriptive correlational, cross-sectional study, in which 120 respondents were recruited by using purposive sampling. Multidimensional Perceived of Social Support (MSPSS) and Dietary Adherence questionnaire was used based upon validity and reliability to measure social support and adherence. Pearson Product-Moment Correlation Coefficient was used to examine the relationship between social support and dietary adherence. The analysis result indicated that respondents who reported low support were 51 respondents (42.5%), and low dietary adherence was 53 respondents (44.2%). The analysis results showed there was a significant positive relationship between social support and dietary adherence among patients with hypertension, in which the power of correlation was moderate (r = 0.49, p < 0.05). Patients with hypertension who perceived higher social support more likely to adhere to the dietary of hypertension. The result suggests that health care providers need to facilitate support from friends, family, and significant others of the patients to achieve optimum dietary adherence.